Evaluation of an item bank for a computerized adaptive test of activity in children with cerebral palsy. - Haley SM; Fragala-Pinkham MA; Dumas HM; Ni P; Gorton GE; Watson K; Montpetit K; Bilodeau N; Hambleton RK; Tucker CA (Physical Therapy, 2009)
BACKGROUND: Contemporary clinical assessments of activity are needed across the age span for children with cerebral palsy (CP). Computerized adaptive testing (CAT) has the potential to efficiently administer items for children across wide age spans and functional levels. OBJECTIVE: The objective of this study was to examine the psychometric properties of a new item bank and simulated computerized adaptive test to assess activity level abilities in children with CP. DESIGN: This was a cross-sectional item calibration study. METHODS: The convenience sample consisted of 308 children and youth with CP, aged 2 to 20 years (X=10.7, SD=4.0), recruited from 4 pediatric hospitals. We collected parent-report data on an initial set of 45 activity items. Using an Item Response Theory (IRT) approach, we compared estimated scores from the activity item bank with concurrent instruments, examined discriminate validity, and developed computer simulations of a CAT algorithm with multiple stop rules to evaluate scale coverage, score agreement with CAT algorithms, and discriminant and concurrent validity. RESULTS: Confirmatory factor analysis supported scale unidimensionality, local item dependence, and invariance. Scores from the computer simulations of the prototype CATs with varying stop rules were consistent with scores from the full item bank (r=.93-.98). The activity summary scores discriminated across levels of upper-extremity and gross motor severity and were correlated with the Pediatric OUTCOMES: Data Collection Instrument (PODCI) physical function and sports subscale (r=.86), the Functional Independence Measure for Children (Wee-FIM) (r=.79), and the Pediatric Quality of Life Inventory-Cerebral Palsy version (r=.74). LIMITATIONS: The sample size was small for such IRT item banks and CAT development studies. Another limitation was oversampling of children with CP at higher functioning levels. CONCLUSIONS: The new activity item bank appears to have promise for use in a CAT application for the assessment of activity abilities in children with CP across a wide age range and different levels of motor severity.